Building Students’ Motivation and Ability in Speaking English: The Use of Cooperative-Instructional Video - Dian Kristin Ningrum; Khoirul Anwar; Agus Wardhono (Universitas Muhammadiyah Gresik, 2023)
Low learning motivation of senior high school students caused by several things including: learning methods that do not adjust with the times and the media does not support or encourage students to be interested in learning. This study attempted to answer those problems by applying the method of cooperative learning which make students actively interact and communicate with their group and using instructional video that does not make them bored in learning so they feel interested and motivated in learning. Most of the previous studies only focus on the impact of using the cooperative strategy or instructional video (choosing one of them) on the teaching-learning process to increase student's ability in a certain skill. But in this study, it is used the combination between cooperative strategy and instructional video in teaching-learning process. Since the study was quasi-experimental, the instruments to collect the data were test and questionnaire. The researcher took two classes as the experimental class= 25 students and the control class= 25 students of the twelfth grade students of SMAN 5 Tuban. The motivation questionnaire using four-point Likert-type scales. Items on the scales are anchored at 1 = strongly disagree, 2 = disagree, 3 = agree and 4 = strongly agree. The result of motivation questionnaire proved that the students are motivated in learning speaking when using cooperative-instructional video than conventional method. The result of T-Test indicates that English learning students on speaking skill taught by using the cooperative-instructional video was better than using the conventional learning method (textbook). This has implication for language teachers who are interested in incorporating technology into their classes, which may contain students with low motivation and their speaking ability. Keywords: students’ motivation in speaking, cooperative learning, instructional video.